Association between falls in older adults and prevention group - Elenir Pereira de Paiva; Maira Amorim da Costa; Tamara Costa Souza; Meire Cavalieri de Almeida; Monalisa Claúdia Maria Novaes da Silva; Fabiano Bolpato Loures (Revista Brasileira de Enfermagem, 2022)
ABSTRACT Objectives: to assess the effectiveness of guidelines on fall prevention in a group of older adults in Primary Health Care. Methods: a cross-sectional study, carried out with older adults selected by a simple random sample (274; N=1,234). Data covered sociodemographic and socioeconomic variables, marital status, health conditions, factors associated with falls and participation in the prevention group. Student’s t test was used, and dichotomous variables were used by the chi-square test. The project met ethical requirements. Results: sample with female profile (61.7%), married, with low education, mean age of 71.69 years. The factors associated with falls identified were female sex, medicalization and participation in the prevention group. There was no protective association between participation in a fall prevention group in older adults and a decrease in the number of falls. Conclusions: based on evidence, a personalized intervention during the nursing visit is suggested as a strategy to prevent falls.